Enhancing the quality of teacher-child interactions in Singapore pre-school classrooms - Nirmala Karuppiah (Journal of Childhood, Education & Society, 2021)
This exploratory study was aimed primarily at developing baseline data on the quality of teacher-child interactions in Singapore pre-school classrooms. Data were collected through observations of teacher-child interactions in 80 pre-schools, using the Classroom Assessment Scoring System (CLASS) in the three key domains which are 1) Emotional Support, 2) Classroom Organisation, and 3) Instructional Support (Pianta, La Paro, & Hamre, 2008). It was found that the overall quality of teacher-child interactions in the Singapore pre-school classrooms was low to moderate, with Instruction Support being the lowest. This finding is similar to that found in studies conducted in many other countries including China and the U.S. (Slot, 2017). Possible reasons and explanations will be presented, and suggestions to improve or enhance the quality of teacher-child interactions will be proposed. This study has implications on pre-school teacher education and professional development as well as government policies and regulations for the Singapore pre-school sector.